The COVID-19 pandemic: impact on NHS England PET-CT services and lessons learnt. Issue 2 (February 2021) - Wong, Wai Lup; Ross, Peter; Peters, Kevin; Frenz, Marion; Hai, Tong; Ridgeon, Alex; Toop, Ralph; Strouhal, Peter; Bomanji, Jamshed
Abstract : Purpose: The purpose of the study was to examine the impact of the first wave of COVID-19 on National Health Service (NHS) 18F-fluorodeoxyglucose positron emission tomography computed tomography (FDG PET-CT) scanning activity across England. Methods: Monthly FDG PET-CT scanning activity was collected from 41/48 NHS England provider sites. Data from 31/41 sites were stratified by nononcology/oncology, cancer type, with lung cancer and lymphoma split into specific indications, turn-around times and delays due to radiotracer. Results: In April and May 2020, a 32 and 31% decrease in activity was observed, a larger decrease for noncancer compared with cancer FDG PET-CT. In June 2020, activity started to recover with 6% fewer scans recorded compared with June 2019. Of the six most common indications, lung and oesophageal cancer had the largest decrease in activity and slowest recovery. Lymphoma and melanoma showed the smallest decrease and fastest recovery. Lung cancer scans for initial diagnosis/staging saw the largest fall and slowest recovery compared with scans for known lung cancer. There was no percentage increase in overall turn-around time compared with the same months in 2019, and no increase in turn-around time of more than 7 working days due to FDG supply during April and May 2020 compared with the 3 previous months. Conclusions: There is no correlation between FDG PET-CT activity (fall and recovery) in England and the ability to provide the service by NHS England. It most likely reflects a combination of changes in health-seeking behaviour, NHS health policy and a decrease in the use of investigations that carry a high risk of COVID-19 transmission.